A Tale of Eleventh-Century Japan : Hamamatsu Chunagon Monogatari - Rohlich, Thomas H. (Book collections on Project MUSE., 2014)
This book is a complete translation of Hamamatsu Chunagon Monogatari, one of the few extant works of monogatari literature of the Heian period Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich sch.